Infantile Myofibroma Presenting as a Large Ulcerative Nodule in a Newborn - Farooq Shahzad; Ava G. Chappell; Chad A. Purnell; Monica Aldulescu; Sarah Chamlin (Case Reports in Pediatrics)
The differential diagnosis of a congenital cutaneous vascular-appearing mass in a newborn is broad and includes both benign and malignant tumors. We report the case of a newborn who presented with an erythematous exophytic skin nodule on the right upper leg. Excision was performed due to ulceration, concern for bleeding, and for diagnosis. Pathology revealed the mass to be an infantile myofibroma. This case highlights the importance of considering a broad differential diagnosis in a newborn with a cutaneous mass. While history, physical exam, and imaging can help diagnose some cases, a biopsy or excision is often needed to distinguish benign lesions from more concerning lesions.